2011
DOI: 10.1039/c1cp20288j
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization of water in protic ionic liquids

Abstract: A mixture of the protic ionic liquid mono-methylammonium nitrate with 1.6 wt% water was investigated from Car-Parrinello molecular dynamics simulations. In contrast to imidazolium-based ionic liquids, the cation possesses strong directional hydrogen bonds to water and all hydrogen bonds in the mixture have a comparable strength. This results in a good incorporation of water into the hydrogen bond network of mono-methylammonium nitrate and a tetrahedral hydrogen bond coordination of water. Hence, one might expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 159 publications
(168 reference statements)
7
69
0
Order By: Relevance
“…Furthermore, it was reported that IL cations can exhibit a depolarization effect on water molecules. Thus, the dipole moment of water decreases with increasing IL concentration in several aprotic and protic ILs [122][123][124] , which can be counteracted in presence of strong hydrogen bond acceptor anions. Another interesting effect is also the formation of carbenes in presence of water 122 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that IL cations can exhibit a depolarization effect on water molecules. Thus, the dipole moment of water decreases with increasing IL concentration in several aprotic and protic ILs [122][123][124] , which can be counteracted in presence of strong hydrogen bond acceptor anions. Another interesting effect is also the formation of carbenes in presence of water 122 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was found that local properties in ILs—like dipole fluctuations—could not be reproduced by static charges (even if they are sophisticated) in force field simulations. However, these play only a role if the treatment of the local behavior is necessary (e.g., IR or RAMAN spectroscopy), while for non‐local properties (e.g., transport properties) a simple charge scaling can be sufficient to account for charge transfer, as discussed in Chapter 4.…”
Section: Intermolecular Forcesmentioning
confidence: 99%
“…[30] Many computational models have been developed that examined changes in IL solvent structure by dissolved water, often over the full concentration range. [31][32][33][34][35] At low water concentration, the models predict that the IL nanostructure is relatively unperturbed, but at high water content the system resembles aqueous solutions of ionic surfactants. However, these studies have overwhelmingly investigated aprotic ILs; largely absent are corresponding studies of PILs and experimental verification of the findings.…”
mentioning
confidence: 99%